Analisis Penggunaan Amtsal (Perumpamaan) dalam Al-Quran : Kajian Sosiolinguistik Arab - Soleh Soleh (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research examines the use of *amtsal* (parables/analogies) in the Quran from an Arabic sociolinguistic perspective. The main focus of the research is to analyze the forms of amtsal, their sociolinguistic functions, and the influence of socio-cultural context in the selection of Quranic amtsal. The research method uses a qualitative approach with descriptive analysis through literature study of primary and secondary sources. The research results show that amtsal in the Quran has three main forms: *musharrahah* (explicit), *kaminah* (implicit), and *mursalah* (free). The sociolinguistic functions of amtsal include educational functions in facilitating understanding of abstract concepts, persuasive functions in influencing attitudes and behavior, and communicative functions in bridging divine messages with socio-cultural contexts. The selection of amtsal is heavily influenced by the socio-cultural context of Arab society, including traditions, social conditions, and psychological aspects. This research contributes to a deeper understanding of the Quran's communication methods and can serve as a reference in developing contemporary learning and da'wah methods.